Clinicoradiographic evaluation of advanced-platelet rich fibrin block (A PRF + i PRF + nanohydroxyapatite) compared to nanohydroxyapatite alone in the management of periodontal intrabony defects - Jayasheela Mallappa; Deepa Vasanth; Triveni Mavinakote Gowda; Rucha Shah; Gunjiganuru Vemanaradhya Gayathri; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2022)
Background: Several bone grafting formulations have been given clinically acceptable outcomes in treating intrabony defects. Platelet rich fibrin (PRF), an autologous platelet concentrate holds potential to be used for regenerative treatment. The purpose of this study was to evaluate clinical and radiographic outcomes in periodontal intrabony defects treated with advanced-PRF block (A PRF + i PRF + nanohydroxyapatite [nHA]) compared to nHA alone. Methods: Twenty-eight sites in chronic periodontitis patients having probing pocket depth (PPD) ≥6 mm and 3 walled intrabony defects (depth of ≥3 mm) were selected, randomly allotted into two groups: Group A was treated with A-PRF block and Group B with nHA (Sybograf™). Clinical parameters including plaque index (PI), gingival index (GI), PPD, relative attachment level (RAL) and radiographically linear and volumetric defect fill were assessed using cone beam computed tomography at baseline and 6 months postoperatively. Results: Intragroup comparison using paired t-test and intergroup comparison using unpaired t-test was done. Group A demonstrated significantly higher reduction in PPD and gain in RAL when compared to Group B (P ≤ 0.05) at the end of 6 months. Similarly gain in bone volume was greater in Group A (0.1 ± 0.05) as compared to Group B (0.04 ± 0.02) (P ≤ 0.05). Conclusion: Advanced-PRF block showed significant clinical and radiographic improvement as compared to nHA alone which depicts that, it may be an ideal graft to be used for the treatment of periodontal intrabony defects.